Acces to Education for School-Age Children in Coastal Areas in Tallo District, Tallo District, Makassar City - Sofyan Sofyan; Yakub Tangdibiri (Edumaspul: Jurnal Pendidikan, 2023)
The problem in this research is access to education for school-age children in coastal areas in Makassar City. The research aims to determine the lack of access to education for school-age children in coastal areas in Makassar City. The type of research used in this research is qualitative descriptive research. The subjects in the research were school-age children from elementary school, middle school, and high school. The supporting subjects of this research are the children's parents and community leaders. The object of this research is access to education for school-aged children. Data collection techniques are interviews, observation, questionnaires, and documentation. Data analysis techniques are carried out by collecting data, reducing data, presenting data, and drawing conclusions. The research results include: (1) education for the community in Tallo Subdistrict has not been a priority, and the school dropout rate in the area is quite high; (2) factors that cause many school-aged children in Tallo Village not to continue their education are limited school facilities, limited funds, lack of parental support, unsupportive social environment, lack of interest in children going to school, and problems with changing domicile; (3) the net enrollment rate at the elementary, middle and high school levels in Makassar City has decreased in recent years; (4) educational program innovation is needed to overcome the problem of access to education for school-age children. One of the policies that needs to be considered is strengthening community-based alternative education programs.